Finger print integrated electronic voting machine using GSM - D.Dileep, Dr. Sujatha (International Journal of Advanced Science and Technology, 2020)
Casting a ballot machines are the complete mix of mechanical, electromechanical, or electronic hardware (counting programming, firmware, and documentation required to program control, and bolster gear), that is utilized to characterize polling forms; to cast and tally votes; to report or show political decision outcomes also to keep up and give any review trail data. The principal casting a ballot machines were mechanical yet it is progressively increasingly normal to utilize electronic democratic machines. In addition, it is additionally significant that a bogus section ought not be made so for this one of the most secure strategies for casting a ballot is utilizing a biometric sensor like a unique finger impression per user. In this venture we will utilize a Fingerprint per user for giving access to the voters just as making a log if the individual has casted a ballot or not. Keywords: Microcontroller, Finger print sensor, GSM, RFID.